Determining the combined effects of three weeks of consumption of HMB supplement and one session of extreme eccentric resistance exercise on the expression rates of myoG and CD56 genes in satellite cells - Elias Kowsari; Alireza Asgari; Hossein Shirvani; Behzad Bazgir; Mostafa Rahimi (Instituto Brasileiro de Pesquisa e Ensino em Fisiologia do Exercício, 2019)
The purpose of the present study was to determine the combined effects of consumption of HMB-FA supplement and one session of extreme Eccentric resistance training on the rate of activation of the satellite cells of mature male rats. To this end, once the preliminary studies were done, eighty Sprague Dowley male rats (Control group: 18 rats; HMB group: 19 rats; Exercise group: 19 rats; Exercise + HMB group: 19 rats) aged eight weeks and weighting 20020 grams were selected for the study. After the course of familiarization on ladders, the daily intake of supplement was started and sustained for three weeks. Once the rats were familiarized with the ladder and the supplement was taken in for three weeks, a session of Eccentric resistance training was administered. The protocol of the training included descending from a ladder with a slope of 80% while a 100-110% 1RM weight was attached to the rats' tails. Results of extraction of RNA and Immunohistochemistry showed that the entire three experimental interventions have resulted in an increase in the expression of the MyoG and CD56 genes in the triceps. The important point however, was that the most effective intervention was the exercise + HMB intervention. The amounts of CD56 and MyoG genes have been statistically significantly increased in the groups of HMB, Exercise and, Exercise + HMB (p= 0.001). According to the obtained results, consumption of HMB supplement in combination with effectuation of Eccentric exercises can play an effective role in the activation, propagation proliferation and differentiation of satellite cells. In fact, athletes and military men whom at some points get involved in heavy physical activities and use extreme Eccentric preparatory training in order to maximize their physical readiness can use HMB supplement simultaneously with their training and get even more efficient results.